PENGEMBANGAN KURIKULUM EKSTRAKURIKULER DALAM MENINGKATKAN MINAT DAN BAKAT SISWA - Muh Idris (Ta'dibi : Jurnal Manajemen Pendidikan Islam, 2023)
Extracurricular activities are one of the student development activities. Extracurricular activities are activities carried out by students outside of class learning hours. Extracurricular activities are divided into mandatory extracurricular activities and optional extracurricular activities, which are followed by students who are interested in these activities. This paper aims to (1) reveal the development of extracurricular curriculum (2) Know how the extracurricular curriculum in increasing students' interests and talents. Extracurricular curriculum development is a program or design of educational activities held outside of class hours held by the school authorities to shape the character of students in supporting the achievement of educational goals. In other words, the extracurricular curriculum is part of the education unit curriculum developed by each educational institution tailored to the needs of the school. Meanwhile, schools can function as a medium for developing and fostering children's interests and talents properly, so that they do not merely present abstract and scholastic knowledge.